Effect of processing on microbial safety of wild pepper (Piper borbonense) from Reunion Island. (May 2020) - Weil, Mathieu; Remize, Fabienne; Durand, Noel; Alter, Pascaline; Hoarau, Mathilde; Meile, Jean Christophe
Abstract: The management of microbial contamination is an important issue in spice trade. For common domesticated black pepper ( Piper spp . ), the control relies mainly on post-process decontamination. The aim of the present study was to examine microbial contamination of wild pepper ( Piper borbonense) from Reunion Island and investigate the effects of different processing paths on microbiological quality and fungal ecology. The fresh pepper microbial counts ranged from 4.6 to 6.8 log CFUg −1 . Blanching had a positive significant impact on the microbiological quality of pepper whereas sweating led to microbial growth up to 5 log CFUg −1 and, therefore, should be avoided. Microbial counts for dried pepper were 1.33 log CFUg −1 ; 3.37 log CFUg −1 ; 1.67 log CFUg −1 and 1.3 log CFUg −1 for coliforms, TAMB, Staphylococcus, yeast and moulds, respectively. Potential mycotoxin producers were identified from pepper samples but aflatoxins and ochratoxin A levels detected were far below the regulation limits. The initial diversity of fungal contamination is prominent for the final quality of pepper in contrast to the impact of processes. The revisited wet process (blanching then drying), which positively affected all microbial loads, could be a good option for pepper transformation. Highlights: Variations in microbial counts and fungal diversity were observed on pepper berries. Blanching was efficient in decreasing microbial counts while drying had a low impact. Sweating lead to an increase in microbial counts and thus should be avoided. Mycotoxins were detected in only one sample and at a very low level.